The Role of Multimodality Cardiovascular Imaging in Peripartum Cardiomyopathy - Ricci, Fabrizio; De Innocentiis, Carlo; Verrengia, Elvira; Ceriello, Laura; Mantini, Cesare; Pietrangelo, Carla; Irsuti, Flaviano; Gabriele, Stefano; D'Alleva, Alberto; Khanji, Mohammed Y.; Aung, Nay; Renda, Giulia; et al. (Frontiers in Cardiovascular Medicine, 2020)
The burden of pregnancy-related heart disease has dramatically increased over the last decades due to the increasing age at first pregnancy and higher prevalence of cardiovascular risk factors such as diabetes, hypertension, and obesity. Pregnancy is associated with physiological changes in the cardiovascular system, including hemodynamic, metabolic and hormonal adaptations to meet the increased metabolic demands of the mother and fetus. It has been postulated that pregnancy may act as a cardiovascular stress test to identify women at high risk for heart disease, where the inability to adequately adapt to the physiologic stress of pregnancy may reveal the presence of genetic susceptibility to cardiovascular disease or accelerate the phenotypic expression of both inherited and acquired heart diseases, such as peripartum cardiomyopathy (PPCM). PPCM is a rare and incompletely understood clinical condition. Despite recent advances in the understanding of its pathogenesis, PPCM is not attributable to a well-defined pathological mechanism and therefore its diagnosis still relies on the exclusion of overlapping dilated phenotypes. Cardiac imaging plays a key role in any peripartum woman with signs and symptoms of heart failure in establishing the diagnosis, ruling-out life-threatening complications, guiding therapy and conveying prognostic information. Echocardiography represents the first line imaging technique given its robust diagnostic yield and its favorable cost-effectiveness. Cardiovascular magnetic resonance is a biologically safe high- throughput modality that allows accurate morpho-functional assessment of the cardiovascular system in addition to the unique asset of myocardial tissue characterization as a pivotal piece of information in the pathophysiological puzzle of PPCM. In this review, we will highlight current evidences on the role of multimodality imaging in the differential diagnosis, prognostic assessment and understanding of the pathophysiological basis of PPCM.